1990
DOI: 10.1111/j.1751-1097.1990.tb04192.x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Electronic Spectra and Photophysics of Uracil Derivatives*

Abstract: The changes that the UV absorption spectrum and the photophysics of uracil undergo under hydrogen substitution or deprotonation, were studied theoretically within the CS-INDO/CI scheme. First of all this method was tested on uracil. It was then used for the calculation of the electronic structure of excited states (Sn, Tn) of a large number of uracil derivatives (1-, 3- and 5-methyluracil; 1,3-, 1,5- and 3,5-dimethyluracil; 5-fluoro- and 5-chlorouracil), including some anions (1- and 3-methyluracil anion). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Polarized absorption, 37 polarized fluorescence, 9 and the reflection experiment 38 indicate that such behavior cannot be attributed to the presence of a nπ* transition lying under ππ* transition. Moreover, all theoretical calculations 9,18 interpreted the first absorption band as a single intense ππ* transition. Therefore, variation in the fluorescence spectrum as a function of the excitation wavelength is most probably due to the presence of at least two different thymine tautomers.…”
Section: Resultsmentioning
confidence: 99%
“…Polarized absorption, 37 polarized fluorescence, 9 and the reflection experiment 38 indicate that such behavior cannot be attributed to the presence of a nπ* transition lying under ππ* transition. Moreover, all theoretical calculations 9,18 interpreted the first absorption band as a single intense ππ* transition. Therefore, variation in the fluorescence spectrum as a function of the excitation wavelength is most probably due to the presence of at least two different thymine tautomers.…”
Section: Resultsmentioning
confidence: 99%
“…Note that there is also the possibility of formation of the Hoogsteen base pair in the case of adenine and thymine or adenine and uracil bases (for the nomenclature, see ref ). The tautomeric equilibria and molecular properties of adenine and uracil and their derivatives in the gas phase and in a polar solution have been discussed in several papers from both experimental and theoretical points of view. Schoone et al studied the relative stabilities of the 1-methyladenine tautomers at the HF/6-31++G level and combined these investigations with matrix-isolation FT-IR spectroscopy . Burda et al reported the results of calculations performed at the HF and MP2 levels of theory on the standard N7 coordination of adenine and guanine with various mono- and divalent metal cations .…”
Section: Introductionmentioning
confidence: 99%
“…For the adenine-thymine base pair, such a proton-transfer process would lead to thymine tautomerization and the mispairing of guanine and thymine tautomer. 8 The biological importance of thymine has motivated a number of experimental [9][10][11][12] and theoretical [13][14][15] investigations.…”
Section: Introductionmentioning
confidence: 99%